Tangible and intangible resources and the financial performance of Polish social cooperatives - Rajchelt-Zublewicz, Magdalena; Piwoni-Krzeszowska, Estera; Matyja, Małgorzata (Materialne i niematerialne zasoby a wyniki finansowe polskich spółdzielni socjalnych, 2019)
The purpose of the article is to determine the relationship between the level of competitiveness of resources and the financial performance of social cooperatives. In the preliminary analysis, based on the results of survey, we use the data provided by 57 respondents. For in-depth analysis we involve the data from the EMIS Intelligence database of 20 Polish social cooperatives. Using the Spearman’s rank correlation we investigate the relationship between the rating of the level of competitiveness of tangible (physical, technological, financial) and intangible (human, relational, knowledge) resources and the cooperatives’ financial performance, i.e. the rating of profitability and revenues. Initially, the research results proved that there are average relationships between the rating of profitability and the rating of competitiveness of tangible (0.38) and intangible (0.42) resources. However in the in-depth analysis, based on objective data, even a weak correlation between either tangible or intangible resources and the revenues was not found. The article also discusses the obtained results along with identifying the likely causes of this situation
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 173-187
Keywords: social cooperatives; tangible resources; intangible resources; zasoby materialne; zasoby niematerialne; wynik finansowy; konkurencyjność